Chemical characterization of floral scents in the six endemic baobab species (Adansonia sp.) of Madagascar. (June 2015) - Razanamaro, Onja; Rasoamanana, Elysée; Rakouth, Bakolimalala; Randriamalala, Josoa Ramarolanonana; Rabakonadrianina, Elisabeth; Clément-Vidal, Anne; Leong Pock Tsy, Jean-Michel; Menut, Chantal; Danthu, Pascal
Abstract: Baobab (genus Adansonia, family Malvaceae) comprises nine species distributed worldwide of which seven are present in Madagascar. Six are endemic to Grande Ile and are distributed in two sections: Brevitubae and Longitubae. The aim of this study was to distinguish the qualitative and quantitative characters of floral emissions by different species of Malagasy baobabs and to propose hypotheses on their modes of pollination. Floral fragrance was analysed using gas chromatography and mass spectrometry. The study revealed two sections which were distinguishable by the quality and quantity of the compounds they emitted. Species belonging to the Longitubae section all emit a large quantity of compounds with aromatic structures, dominated by 2-phenylacetonitrile, whereas the fragrances of the two species of Brevitubae are rich in compounds with aliphatic structures, particularly 8-heptadecene. The majority of chemicals identified in the Longitubae section are common components of a wide array of scented flowers pollinated by moths such as Sphingidae. However, in the Brevitubae section, no clear relation was found between chemical composition of the fragrance and a particular type of pollinator. The presence of common components in the fragrances in every Longitubae species made it possible to analyse the action of common pollinators and to explain the cases of genetic introgression between the species in this section. Highlights: Longitubae are dominated by aromatic structures particularly 2-phenylacetonitrile. Brevitubae are rich in compounds with aliphatic structures such as 8-heptadecene. Common compounds can explain the cases of genetic introgression between the species.